THE EFFECT OF ORGANIZATIONAL JUSTICE AND SELF EFFICACY ON KNOWLEDGE SHARING IN M-19 SHOP AT MANADO - David, Fikran .; Lapian, S.L.H.V. Joyce; Pandowo, Merinda . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: This study objectives are to analyze the influence of organizational justice and self efficacy on knowledge sharing simultaneously and partialy in M-19 Shop at Manado. This research type is causal uses quantitative type of research. This study is conducted in M-19 Shop at Manado. This research was held at 2018. This research use employees as respondents. Sample of this research are 35 employees. Data analysis using validity and reliability test and regression analysis and hypothesis test. This research finding are: organizational justice, and self efficacy has a positive and significant influence on knowledge sharing. Organizational justice and self efficacy has significant and positive impact on knowledge sharing partialy. Organizational justice has the highest impact variable that influence knowledge sharing comparing to other variable. Self efficacy has the second highest impact variable that influence knowledge sharing. Suggestion of this research: organization in this research must pay attention to this research finding. Organization in this research must improve organizational justice or organizational fairness also self efficacy to improve knowledge sharing in organization. Keywords: Organizational justice, self efficacy, knowledge sharing, small medium enterprises